2013
DOI: 10.5152/jtgga.2013.62347
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parity on perinatal outcomes in pregnancies complicated by advanced maternal age

Abstract: Objective:The purpose of this study was to investigate the impact of parity on perinatal outcomes in pregnancies complicated by advanced maternal age. Material and Methods:A total of 11 587 pregnancies were reviewed retrospectively from patient medical records. Singleton pregnancies greater than 24 weeks of gestation were included. The study group consisted of women ≥40 years old at the time of delivery, and the control group consisted of women aged between 20 and 30 years old. Data regarding age, parity, gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 16 publications
6
27
0
8
Order By: Relevance
“…In a study by Başer et al, for advancing age pregnancy (>40 years) the NICU admission rate was almost twice in nullipara (15.2%) as compared to multipara (5.7%), whereas in mothers aged 20-30 years the rate of NICU admission was lower in nullipara (6.9%) as compared to multipara (8.9%). 15 Although, none of the mothers in present study were aged >40 years and as such proportional distribution of multipara to nullipara in present study (54/46; 1.17:1) is similar to that reported in the cited study (1.29:1). Pregnancy induced hypertension is a known risk factor for NICU admission.…”
Section: Discussionsupporting
confidence: 87%
“…In a study by Başer et al, for advancing age pregnancy (>40 years) the NICU admission rate was almost twice in nullipara (15.2%) as compared to multipara (5.7%), whereas in mothers aged 20-30 years the rate of NICU admission was lower in nullipara (6.9%) as compared to multipara (8.9%). 15 Although, none of the mothers in present study were aged >40 years and as such proportional distribution of multipara to nullipara in present study (54/46; 1.17:1) is similar to that reported in the cited study (1.29:1). Pregnancy induced hypertension is a known risk factor for NICU admission.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have shown an association between AMA and gestational complications, such as gestational diabetes, gestational hypertension, C-section, preeclampsia, premature rupture of membranes, and chromosomal fetal anomalies 9,10,11,12,13,14 . However, the evidence is inconclusive regarding the association of AMA with placenta praevia (PP) and placental abruption (PA), with some studies indicating a positive association 12,14,15,16 and others showing no statistically significant association 13,17,18,19,20,21,22,23,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Sekeroglu et al (17) and Baser et al (18) reported that higher maternal age is associated with decreased APGAR scores and poor neonatal outcomes. In this study maternal age was negatively correlated with 1 th minute-APGAR scores but there was no significant correlation with 5 th minute APGAR scores, and material age.…”
Section: Resultsmentioning
confidence: 99%